Comparative study of efficacy of excimer light therapy vs. intralesional triamcinolone vs. topical 5% minoxidil for alopecia areata: an observational study - Sanga, Zo Nun (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Alopecia areata (AA) is a chronic inflammatory disease that involves hair follicles, and sometimes nails, caused by a T-cell mediated autoimmune mechanism. Current treatment modalities include corticosteroids (oral, topical or intralesional), minoxidil, contact sensitizers (DNCB, DPCP and SADBE), immunosuppressants (methotrexate or azathioprine), DMARDs (sulfasalazine), and phototherapy. Objective. To compare the efficacy of excimer light therapy, intralesional triamcinolone and 5% topical minoxidil. Material and methods. After taking consent, 40 patients were treated with excimer light, 46 patients with intralesional triamcinolone injection and 14 patients with 5% topical minoxidil. The results were compared by their photographs taken prior to treatment, at 2 months and 6 months of follow-up. Results. Among the excimer group, 21/32 (61.76%) patients with a single patch and 1/6 (16.67%) with multiple patches achieved > 50% hair regrowth. In the triamcinolone group, 23/30 (76.67%) with a single patch and 10/16 (62.5%) with multiple patches achieved > 50% hair regrowth, and in the minoxidil group, 4/12 (33.33%) with a single patch and none, i.e. 0/2, with multiple patches achieved > 50% regrowth. Conclusions. After comparing the efficacy of excimer light therapy, intralesional triamcinolone and 5% minoxidil, it was concluded that intralesional triamcinolone seems to be the most efficacious. Multiple AA patches were more resistant than a single patch. Scalp response was much better than beard.